Pengembangan mie sagu ikan aneka warna dan rasa di Desa Banglas Barat Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti - Dewita Dewita; Syahrul syahrul; Hendrik Hendrik; Suardi Loekman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Kepulauan Meranti regency is one of the centers of sago production and fish in Riau Province even at the national level. Sago noodles are the region’s leading food products with a proximate composition high carbohydrates and low protein. The objectives of this PKM activity are (1) to transfer the technology of processing various-colored fish and sago noodles, (2) introducing the technology of processing sago noodles fortified with fish and shrimp concentrates, and (3) increasing the nutritional value of various colors and flavors of fish sago noodles as regional superior products. The method used is the method of active participation learning system with phases: (1) The preparation phase, which is to approach the partners and explain the purpose of implementing PKM activities. (2) The implementation phase, which is providing counseling and training to Partners. The technology transfer given is the processing of various colors and flavors of fish sago noodles, then one month of assistance is carried out which ends the evaluation phase of the activity. The results obtained are activities have taken place well, and partners have had direct experience in the transfer of technology in the production of various colors and flavors of fish sago noodles. This activity has been able to provide enlightenment and insight to partners about product and business development. Technology transfer activities resulted in participants’ responses to counseling and training of the target audience that 90% was very helpful and 10% could help.